(untitled) - Beatty, Ken (New York, 2010)
Computers play a crucial and rapidly evolving role in education, particularly in the area of language learning. Far from being a tool mimicking a textbook or teacher, Computer-Assisted Language Learning (CALL) has the power to transform language learning through the pioneering application of innovative research and practices.
Ứng dụng công nghệ thông tin trong dạy học Tiếng Anh
Keywords: Ngôn ngữ,Language and languages; Chỉ dẫn hỗ trợ máy tính,Computer-assisted instruction